2018
DOI: 10.1111/bdi.12693
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis with MOODS‐SR illustrates a potential bipolar disorder risk phenotype in young adults with remitted major depressive disorder

Abstract: Objectives: Delays in the diagnosis and detection of bipolar disorder can lead to adverse consequences, including improper treatment and increased suicide risk. The Mood Spectrum Self-Report Measure (MOODS-SR) was designed to capture the full spectrum of lifetime mood symptomology with factor scores for depression and mania symptom constellations. The utility of the MOODS-SR as a tool to investigate homogenous subgroups was examined, with particular focus on a possible bipolar risk subgroup. Moreover, potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Those with higher/normative5-HT 1A BP ND 5-HT 1A BP ND levels tended to have worse Negative Memory Bias, Inhibitory Control, and increased BOLD recruitment for successful rejection of prepotent stimuli. Although the sample is quite small, these results reaffirm with other work that there likely many circuits, neurotransmitters, and behaviors associated with subtypes of MDD that are heretofore unclear (Webb et al, 2016; Kling et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Those with higher/normative5-HT 1A BP ND 5-HT 1A BP ND levels tended to have worse Negative Memory Bias, Inhibitory Control, and increased BOLD recruitment for successful rejection of prepotent stimuli. Although the sample is quite small, these results reaffirm with other work that there likely many circuits, neurotransmitters, and behaviors associated with subtypes of MDD that are heretofore unclear (Webb et al, 2016; Kling et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Studies comparing intrinsic connectivity in patients with unipolar and bipolar depression (or those at risk) support this finding, suggesting that increased DMN connectivity represents both a predictor of depression treatment response across mood disorders, 49 and a feature that distinguishes unipolar from bipolar risk in young adults with remitted depression. 54 Other studies have suggested that hyperactivity of VLPFC and stronger connectivity to other high-order networks important for emotion regulation and executive control may represent a biomarker of adaptation toward more resilient outcomes, buffering high-risk offspring from developing BD. 13,55 It is the interpretation of increased strength of VLPFC connectivity as compensatory for early mood symptoms in these HR youths that brings the treatment groupÀby-time interaction finding into context.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 The manic mood domain in particular discriminates between individuals with BD vs unipolar depression, 11 , 13 , 14 highlighting the potential of this scale to screen for mania/hypomania and thus BD-specific risk in young adults on the BD spectrum, some of whom might already be diagnosed with unipolar depression. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…The few studies assessing neural markers of mania/hypomania risk in young adults reported similar findings of reward-related striatal and SN (insula) and emotional regulation–related amygdala hyperactivity in individuals who were hypomania prone vs control individuals 36 , 37 ; positive associations between mania/hypomania risk (measured by the MOODS-SR) and SN activity during reward processing 38 , 39 ; and reduced resting-state functional connectivity between the ventral striatum and CEN regions in individuals at highest risk for BD. 15 Studies in familial at-risk populations (eg, offspring of individuals affected by BD) and youth affected by BD similarly reported altered amygdala, striatal, CEN, and VAN or SN activity and altered amygdala-VAN and amygdala-SN functional connectivity during emotion processing and emotional regulation. 40 , 41 , 42 , 43 Yet, although childhood-onset BD is a more severe form of BD, 44 it is less common than adult-onset BD.…”
Section: Introductionmentioning
confidence: 99%